1998
DOI: 10.1103/physrevlett.81.437
|View full text |Cite
|
Sign up to set email alerts
|

Phase Dependent Thermopower in Andreev Interferometers

Abstract: We report measurements of the thermopower S of mesoscopic Andreev interferometers, which are hybrid loops with one arm fabricated from a superconductor (Al), and one arm from a normal metal (Au). S depends on the phase of electrons in the interferometer, oscillating as a function of magnetic flux with a period of one flux quantum (= h/2e). The magnitude of S increases as the temperature T is lowered, reaching a maximum around T = 0.14 K, and decreases at lower temperatures. The symmetry of S oscillations with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
152
6

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(173 citation statements)
references
References 15 publications
(14 reference statements)
15
152
6
Order By: Relevance
“…However, there are some experimental results 8,14 where the latter symmetry does not hold. Such observations cannot be explained with the quasiclassical theory applied here.…”
Section: Figmentioning
confidence: 92%
See 1 more Smart Citation
“…However, there are some experimental results 8,14 where the latter symmetry does not hold. Such observations cannot be explained with the quasiclassical theory applied here.…”
Section: Figmentioning
confidence: 92%
“…in terms of the biases ∆V j = V j −V , ∆T j = T j −T and the modified response coefficients L. The proximityinduced changes in the conductance 8,9,10,11,12,13,14,15,16,17 have recently been investigated both experimentally and theoretically. Behavior of the remaining off-diagonal coefficient L ij 21 has previously been discussed in Ref.…”
mentioning
confidence: 99%
“…4.6, this symmetry may be violated when electron-phonon or electron-electron interactions are taken into account. Non-symmetric thermopowers have been reported in measurements for certain orientations of a bismuth crystal [152] and in Andreev interferometer experiments [58] (for a theoretical analysis of these latter experiments see [74]). …”
Section: B)s(b B B)s(−b B B) κ(B B B) T = σ (B B B)s(b B B)π (B B B) mentioning
confidence: 99%
“…Therefore, this symmetry may be violated when electron-phonon and electron-electron interactions are taken into account. While the Seebeck coefficient has always been found to be an even function of the magnetic field in two-terminal purely metallic mesoscopic systems [20], Andreev interferometer experiments [21] and recent theoretical studies [22,23] have shown that systems in contact with a superconductor or with a heat bath can exhibit nonsymmetric thermopowers. It is a challenging problem to find realistic setups with x significantly different from unity, while approaching the Carnot efficiency.…”
Section: Reduces To Eq (5) While Thermodynamics Does Not Impose Anymentioning
confidence: 99%